Alterations of Functional Brain Connectivity After Long-Duration Spaceflight as Revealed by fMRI - Pechenkova, Ekaterina; Nosikova, Inna; Rumshiskaya, Alena; Litvinova, Liudmila; Rukavishnikov, Ilya; Mershina, Elena; Sinitsyn, Valentin; Van Ombergen, Angelique; Jeurissen, Ben; Jillings, Steven; Laureys, Steven; Sijbers, Jan; et al. (Frontiers in Physiology, 2019)
The present study reports alterations of task-based functional brain connectivity in a group of 11 cosmonauts after a long-duration spaceflight, compared to a healthy control group not involved in the space program. To elicit the postural and locomotor sensorimotor mechanisms that are usually most significantly impaired when space travelers return to Earth, a plantar stimulation paradigm was used in a block design fMRI study. The motor control system activated by the plantar stimulation involved the precentral and postcentral gyri, SMA, SII/operculum, and, to a lesser degree, the insular cortex and cerebellum. While no postflight alterations were observed in terms of activation, the network-based statistics approach revealed task-specific functional connectivity modifications within a broader set of regions involving the activation sites along with other parts of the sensorimotor neural network and the visual, proprioceptive and vestibular systems. The most notable findings included a postflight increase in the stimulation-specific connectivity of the right posterior supramarginal gyrus with the rest of the brain; a strengthening of connections between the left and right insulae; decreased connectivity of the vestibular nuclei, right inferior parietal cortex (BA40) and cerebellum with areas associated with motor, visual, vestibular and proprioception functions; and decreased coupling of the cerebellum with the visual cortex and the right inferior parietal cortex. The severity of space motion sickness symptoms was found to correlate with a post- to preflight difference in connectivity between the right supramarginal gyrus and the left anterior insula. Due to the complex nature and rapid dynamics of adaptation to gravity alterations, the postflight findings might be attributed to both the longterm microgravity exposure and to the readaptation to Earth’s gravity that took place between the landing and postflight MRI session. Nevertheless, the results have implications for the multisensory reweighting and gravitational motor system theories, generating hypotheses to be tested in future research.